PERFORMANCE MANAGEMENT THROUGH COMPENSATION SYSTEM AND CAREER MANAGEMENT: ACCELERATING ORGANIZATIONAL EXCELLENCE SUSTAINABILITY IN PT PJB SURABAYA - Darmasetiawan, Noviaty Kresna (Penerbit Atma Jaya Catholic University of Indonesia, 2017)
Performance management is becoming a major requirement for many organizations, due to a good performance management of an organization can make it easier to achieve objectives, further impacts are as an advantage acceleration of sustainable organizations.   PT. PJB Surabaya conducts performance management through the creation of a compensation system and employee career management. Compensation system that is applied is in the context of employee performance management is through a system of remuneration and incentives for the employees, while the management system of the careers of employees are done transparently and equitable for every employee to prepare the employees who have integrity and high competence, and professional in carrying out the companys vision and mission. The purpose of this study was to determine how performance management is conducted by PT PJB Surabaya, as well as how is the designs of the compensation system and career management that are conducted by PT PJB Surabaya in order to do the performance management. This research is a study case, which uses primary and secondary data. Primary data were obtained through questionnaires, in-depth interviews and focus group discussions, while secondary data obtained through observation and analysis of documents. The findings obtained from this research is to know about the compensation system and career management that are conducted for performance management of employees, so PT PJB Surabaya is capable of accelerating sustainable organizational excellence.